1983
DOI: 10.1111/j.1600-0528.1983.tb01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dental health care instruction on knowledge, attitude, behavior and fear

Abstract: A field experiment was done to assess the effects of two methods of dental health instruction on knowledge, attitude, reported behavior and fear. Subjects (n=108) were male and female inhabitants of Abcoude, a suburban Dutch village of about 7000 inhabitants. There were three conditions, two experimental and one control. Subjects of experimental condition 1 were given a 30-min personal instruction on dental hygiene, subjects of experimental condition 2 received the same instruction preceded by a 10-min instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
2
5
1
Order By: Relevance
“…Similarly, although the comparison must be inexaet, the pereent of correct answers on knowledge scales in this study was higher than knowledge pretest scores reported in two studies from earUer in the 1980s where dental attendance status of subjeets was not reported (10,11), The scores are similar to those reported recently for a small group of patients receiving treatment in a periodontal research center (13), Also, although comparison again must be only approximate.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similarly, although the comparison must be inexaet, the pereent of correct answers on knowledge scales in this study was higher than knowledge pretest scores reported in two studies from earUer in the 1980s where dental attendance status of subjeets was not reported (10,11), The scores are similar to those reported recently for a small group of patients receiving treatment in a periodontal research center (13), Also, although comparison again must be only approximate.…”
Section: Discussionsupporting
confidence: 76%
“…The classic health belief model, which has provided much of the rationale for patient edueation, was based upon the premise that health related behavior was determined by an individual's beliefs concerning susceptibility, disease severity, and beneficial effects of the behavior (2), Currently, patient knowledge and beliefs are seen as playing a less crucial, but still important, role in the adoption of preventive health behaviors (3,4), Our knowledge of these attributes is incomplete (5), Information about knowledge and beliefs eoneerning periodontal disease is particularly lacking. Since 1980, only eight studies have incorporated adults' knowledge or beliefs about periodontal disease as dependent or independent variables (6)(7)(8)(9)(10)(11)(12)(13). Methods and disaggregated results are fully described in only four of these studies (6)(7)(8)(9), wherein most respondents were generally aware of periodontal disease while up to 50% held incorrect specific information about its prevention and treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in recent decades have demonstrated the positive effects of various measures, individual and group based, aiming at influencing the behaviour of individuals towards promotion of improved oral health (Ryant & Sheiham 1980, Tan et al 1981, Hoogstraten & Moltzer 1983, Schou 1985, Moltzer & Hoogstraten 1986, Glavind 1990, Stewart et al 1991, Nowjack‐Raymer et al 1995, Axelsson et al 2004).…”
mentioning
confidence: 99%
“…Four systematic reviews reported on the impact of dietary interventions conducted in the dental setting (Dyer & Robinson 2006, Harris et al 2012, Cascaes et al 2014, Gao et al 2014). They included a total of six studies (Hoogstraten & Moltzer 1983, Wennerholm et al 1995, Brunner et al 1997, Kay & Locker 1998, Bradbury et al 2006, Hausen et al 2007). Moderate strength of evidence was found that one-to-one dietary interventions provided in the dental set-ting aiming to change fruit and vegetable consumption can change behaviour.…”
Section: Dietary Interventionsmentioning
confidence: 99%